THE EFFECTIVENESS OF USING QUESTIONING THE AUTHOR STRATEGY IN TEACHING READING COMPREHENSION OF RECOUNT TEXT - Fibriana, Anis (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research is a pre-experimental design on Teaching Reading Comprehension to Students of Junior High School. The aim of this research is to see the effectiveness of using Questioning the Author strategy in teaching reading comprehension of recount text. This research was conducted to the eighth grade students of Madrasah Tsanawiyah Swasta Darul Ulum Pontianak. The population of this research was 128 students, which consist of class A, B, C and D. The sample of this research was class B with 33 students. The selection of this sample used the purposive sampling technique. This research covers dependent variable (students’ reading comprehension achievement) and independent variable (the use of QtA strategy). There were three times of treatment (teaching process) conducted by the researcher based on the procedures of pre-experimental design. The use of QtA strategy indicated that the students’ achievement on reading comprehension of recount text was improved and it was found that the students had good enough enthusiasm and understanding in reading text through this strategy. It was also proved that the significant score of students’ achievement was 5.7. The size effect of the use of QtA strategy toward the students’ reading comprehension achievement of the recount text was 20.8. This result indicated that the use of QtA strategy strongly improved the students’ reading comprehension of the recount text. The interpretation of hypothesis of this research, the null hypothesis was rejected because the result of t-test score was higher than t - table. Therefore, the alternative hypothesis was accepted in this research.Keywords: Questioning the Author Strategy, Reading Comprehension, Recount Text.